Geographic information systems (GIS) for disaster management - Tomaszewski, Brian (Boca Raton, FL : CRC Press, 2015)
'... [P]rovides coverage of the basics of GIS. It examines what GIS can and can't do, GIS data formats (vector, raster, imagery), and basic GIS functions including analysis, map production/cartography, and data modeling. It presents a series of real-life case studies that illustrate the GIS concepts discussed in each chapter. These case studies supply readers with an understanding of the applicability of GIS to the full disaster management cycle.' -- back cover.
Includes bibliographical references and index.
Keywords: Geographic information systems; Disaster relief -- Geographic information systems; Emergency management -- Geographic information systems